Trans-Anethole Alleviates Subclinical Necro-Haemorrhagic Enteritis-Induced Intestinal Barrier Dysfunction and Intestinal Inflammation in Broilers - Yu, Caiyun; Wang, Dong; Tong, Yichun; Li, Qiming; Yang, Weiren; Wang, Tian; Yang, Zaibin (Frontiers in Microbiology, 2022)
This study investigated the alleviative potential of trans-anethole (TA) on the impaired intestinal barrier and intestinal inflammation and its regulatory effects on gut microbiota in broilers with subclinical necro-hemorrhagic enteritis (NE) challenge. Subclinical NE challenge led to a severe decline in the 21-day body weight (BW) and average daily gain (ADG), but an increase in feed conversion ratio (FCR) and intestinal lesion score of birds compared with controls (P < 0.05). Compared with the subclinical NE group, the TA administration group exhibited lower (P < 0.05) intestinal lesion score and crypt depth (CD), serum diamine oxidase activity, and D-lactate concentration, but higher (P < 0.05) intestinal tight junction protein expressions, villus height (VH), VH/CD, and numbers of proliferating cell nuclear antigen (PCNA)-positive cells. The administration of TA also inhibited (P < 0.05) the expression of intestinal pro-inflammatory cytokines including interleukin (IL)-1β, IL-8, interferon-gamma (IFN-γ), and tumor necrosis factor-alpha (TNF-α) but increased (P < 0.05) jejunal IL-10 and secretory immunoglobulin A (sIgA) concentration. TA inclusion also led to a remarkable reduction of intestinal NF-kappa-B inhibitor alpha (IκBα) degradation and nuclear factor kappa beta (NF-κB) translocation. Moreover, TA modulated the cecal microbiota abundance and diversity of NE birds, as confirmed by reducing the phylum Firmicutes and genera Ruminococcaceae_UCG-014, Eubacterium_coprostanoligenes_group, and Ruminococcaceae_NK4A214_group when supplemented at 600 mg/kg and reducing genera Butyricicoccus, Oscillibacter, and Flavonifractor when supplemented at 400 mg/kg (P < 0.05). Supplementation of TA in broiler diets could alleviate subclinical NE infection by restoring intestinal barrier integrity, inhibiting NF-κB signaling pathway, and modulating gut microbiota. A 600-mg/kg dose of TA is the optimum concentration for ameliorating subclinical NE in broilers.